Antifungal Effects of Plant Extracts on Colletotrichum gloeosporides in Chilli Pepper (Capsicum frutescens L.) - Awanda Zidni Rizki; Fery Abdul Choliq; Mintarto Martosudiro (Journal of Tropical Plant Protection, 2021)
Chili pepper (Capsicum frutescens L.) is a horticultural commodity that has high economic value and has the potential as an export commodity. One of the factors causing the decrease in productivity of chilli pepper is anthracnose caused by C. gloeosporioides. Consequently, plant-based fungicides might be served as eco-friendly alternatives to control C. gloeosporioides. This study aimed to invesitigated the effect of plant extracts from clove flowers, fennel seeds, basil, sweet basil, and citronella on growth inhibition of C. gloeosporioides in-vitro and in-vivo. Data were analyzed using Analysis of Variance (ANOVA). The five plant extracts were able to inhibit the growth of the pathogen C. gloeosporioides in vitro and in vivo. The highest inhibition of the pathogen C. gloeosporioides was basil extract treatment in-vitro compared to the control treatment. The in-vivo treatment, the lowest growth of C. gloeosporioides in fennel extract and was significanly different compared to the control treatment.